VOCABULARY ENHANCEMENT THROUGH MEMRISE AND GOOGLE CLASSROOM - Stephanie Feli Taebenu; Caroline V. Katemba (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
Google Classroom is one of the most used learning platforms during this Covid-19 pandemic at school, especially in Indonesia. Besides that, another application is used to make the English classes attractive and interesting. Memrise application is used in this study as an addition to google classroom. Therefore, the purpose of this study is to see if there is a significant difference in vocabulary enhancement between females and males using Google Classroom and Memrise. This study employed a quantitative research method and a comparative design with pre-test and post-test. The sample size for this study was 40 students. The students were divided into two groups, with those two groups there were 20 female and 20 male students. The result of this study showed that both groups of students could enhance their vocabulary ability but, the female group result showed a significantly higher enhancement compared to the male group. Another result showed there was a significant difference in vocabulary enhancement between students who were taught using Memrise through Google Classroom in the female and male groups. In summary, the findings indicated that Memrise was effective in helping students to enhance and enrich their vocabulary.